Analisis Penegakan Kebiri Kimia Bagi Pelaku Tindak Pidana Kekerasan Seksual Pada Anak Di bawah Umur - Imas Novita Juaningsih (JOURNAL of LEGAL RESEARCH, 2019)
Abstrak Country can be said to be a state if elements of the state have been fulfilled. One of the most fundamental elements is the existence of the people. The existence of the people means that there are people who live and become subjects of government and enforced rules. Without rules, the consequence is that there will be a large number of crimes that cannot be overcome. Therefore criminal law exists to optimize a regulation and implementation in the community. In the constitution of the Indonesian state, there has been guaranteed the rights of everyone from the right to life, the right not to be tortured, the right to religion and human rights that cannot be reduced in any case. But with Article 81 A paragraph (3) of Law No. 17 of 2016 concerning the second amendment to Law No. 3 of 2002 concerning Child Protection. In this article the phrase the addition of basic crimes especially chemical castration punishment becomes a problem that causes controversy among the public. So the government needs to reconsider with regard to Article a quo by using preventive and repressive measures to address these problems.  The theory that author use is Law Enforcement along with the principles of das sein and das sollen. With normative research methods that are descriptive, and through a conceptual approach. So the author recommend that the application of chemical castration and rehabilitation as a form of treatment oriented to protect perpetrators and sexual crimes.